(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
MSMEs, which stand for micro, small, and medium-sized firms, are crucial to the capacity ofan economy to grow in a sustainable manner and to provide new employment opportunities. It isstandard practise to see this industry as the primary agent of economic growth and social advancementnot just in industrialised nations but even in emerging ones as well.The micro, small, and medium-sizedcompanies (MSME) of Bihar have been a major contributor to the state’s robust economic growth inrecent years. Because to their efforts, the economy of the nation as a whole has expanded in a moreequitable manner, as have the exports of the country, the number of new employment, and the regionaldisparities that existed prior to their work. Despite substantial infrastructural deficiencies and limits suchas a restricted flow of institutional finance and inadequate market ties, the sector has shownextraordinary performance in terms of population growth, investment volume, production size, and totalcontribution to the state’s GDP. This is the case despite the fact that it has been confronting thesechallenges. The primary objective of this research is to draw attention to the bright future that lies aheadfor Bihar’s MSME sector by bringing to light the immense growth potential that exists within the state. Inaddition to this, it attempts to identify significant issues and provide potential solutions.